Developing the Croatian National Corpus and Beyond - Tadić, Marko (2006)
The Croatian National Corpus (HNK) has been collected since 1998 under grant #0130418 by the Ministry of Science and Technology of the Republic of Croatia. The theoretical foundations for such a corpus was laid down in Tadić (1996, 1998), where the need for a Croatian reference corpus (both synchronic and diachronic) was expressed. The tentative solution for its structure was suggested, its time-span and size as well as its availability over the WWW further elaborated. The usage of this corpus data in quantitative analysis of Croatian is discussed.
Projekt MZOS
ENG